The Effect of Facilities and Training on Employee Performance, with Organizational Commitment as an Intervening Variable - Eka Puspita Sari; Mahmud Mahmud; Fahrul Mauzu (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the direct and indirect effects of workplace facilities and training on employee performance, with organizational commitment as an intervening variable. Research Method: Using an explanatory quantitative approach, this study employed a population of 120 active employees at the Dompu Regency Education, Youth, and Sports Office, with saturation sampling (census). Primary data were collected via a Likert-scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Results and Discussion: Workplace amenities and training have been shown to have a positive and significant impact on employee performance. Training also significantly increases organizational commitment, which, in turn, positively impacts performance; thus, commitment partially mediates the training-performance relationship. However, workplace amenities do not significantly affect organizational commitment, so their mediating effect on this relationship is rejected. Implications: Local government administrators with limited regional budgets are advised to prioritize investment in human capital (training) to boost the skills and long-term commitment of civil servants. Future studies are recommended to explore the moderating effects of leadership styles. Originality: This study offers a novel perspective by examining the limitations of the Resource-Based View in the post-autonomy local public sector, empirically demonstrating that tangible assets (infrastructure) do not automatically translate into intangible assets (affective commitment) without a personal approach.